Characteristics and Driving Mechanism of Soil Organic Carbon Content in Farmland of Beijing Plain: Implication for the Fate of Engineered Polymers in Soil - Lanlan Zhang; Zhen Li; Shiwen Zhang; Shasha Xia; Hongguang Zou; Yuanfang Huang (Advances in Polymer Technology)
Soil organic matter (SOM), as a kind of natural polymers, affects the migration and transport of ions and particles in soil system due to its surface characteristics and interaction and then causes significant changes in soil quality such as soil fertility loss and pollutant transfer. It is of great importance to study the temporal and spatial evolution of soil organic matter and its driving mechanism for soil health management. This study aims to fully reveal the evolution characteristics and driving mechanism of soil organic carbon (SOC) in farmland of the Beijing plain based on a six-year site monitoring. According to the research results, there is a significant difference in the overall soil organic content during the 6-year period. The temporal stability of SOC is moderate, and it is inversely proportional to SOC content in terms of spatial distribution. SOC content increases as organic fertilizer input rises, and an extra unit (15 kg·ha−1) of organic fertilizer input leads to an increase of 0.057 g·kg−1 in SOC content. The soil with higher clay content exhibits higher SOC content. The organic carbon content in different soil texture types increases with time, and there is a significant difference between the increases in medium loam and light loam. The grain field plantation system exhibited declining SOC content, while the protected vegetable fields, open vegetable fields, and orchards all showed an increase in SOC content. According to our results, the SOC content of farmland in the plain areas of Beijing is largely dependent on the input of organic carbon if other conditions remain unchanged or exhibit insignificant changes.